Pengaruh Electronic Word of Mouth (E-WOM) dan Brand Image Terhadap Keputusan Pembelian pada Pengguna Tokopedia - Dhea Eka Vitaloka Khoirunnisa; Sintya Dini Wilanda; Shinta Nurliana; Khairani Zikrinawati; Zulfa Fahmy (Universitas Katolik Widya Karya Malang, 2023)
This study aims to determine the effect of electronic word of mouth (E-WOM) and brand image on purchasing decisions among Tokopedia e-commerce users. This study uses a quantitative research design with data collection techniques in the form of purposive sampling. The subjects in the study totaled 174 respondents who were users of the e-commerce application Tokopedia who had made at least one purchase aged 17-60. The results showed that the electronic word of mouth (E-WOM) variable had a significant effect on purchasing decisions on Tokopedia e-commerce. This is evidenced by the results of the tests that have been carried out obtained t count of 3.126 > 1.973 t table. Brand image variable also has a significant influence on purchasing decisions. This is evidenced by the results of the tests that have been carried out obtained t count of 18.362 > 1.973 t table